THE RESEARCH ACTIVITY OF MYHAYLO HRUSHEVSKY LVIV HISTORICAL SCHOOL ( 1894-1944 ) - Голобін, В. М.; Кісь, Я. І.; Педич, В. П. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Idea, 2019)
The article revealed the problem of the scientific training of national historians in the late 19-early 20 centuries in Galychyna. The main attention is paid to the history of foundation of the science school under the lead of Myhaylo Hrushevsky. The main tendencies of the research activity of the leading historians of Lviv university and "History and Philosophy" section of Shevchenko Scientific Society are analysed in the proceedings.